The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fpsyg.2014.01519
|View full text |Cite
|
Sign up to set email alerts
|

Children do not exhibit ambiguity aversion despite intact familiarity bias

Abstract: The phenomenon of ambiguity aversion, in which risky gambles with known probabilities are preferred over ambiguous gambles with unknown probabilities, has been thoroughly documented in adults but never measured in children. Here, we use two distinct tasks to investigate ambiguity preferences of children (8- to 9-year-olds) and a comparison group of adults (19- to 27-year-olds). Across three separate measures, we found evidence for significant ambiguity aversion in adults but not in children and for greater amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 43 publications
5
27
1
Order By: Relevance
“…However, ambiguity attitudes (known outcomes but unknown probabilities) showed nonlinear developmental trends, with ambiguity tolerance peaking in adolescence. This finding is in line with two previous studies that also found adolescents to be more tolerant of ambiguity than adults2022, but contradicts another recent study suggesting that children may be even more ambiguity tolerant24. More importantly, we found a similar nonlinear developmental trajectory in respondents’ uncertainty attitude.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, ambiguity attitudes (known outcomes but unknown probabilities) showed nonlinear developmental trends, with ambiguity tolerance peaking in adolescence. This finding is in line with two previous studies that also found adolescents to be more tolerant of ambiguity than adults2022, but contradicts another recent study suggesting that children may be even more ambiguity tolerant24. More importantly, we found a similar nonlinear developmental trajectory in respondents’ uncertainty attitude.…”
Section: Discussionsupporting
confidence: 90%
“…At the same time, two recent studies suggest that adolescents are more ambiguity seeking than adults2022 (but see ref. 23), and another study suggests that young children may be ambiguity neutral24. However, no previous studies have elicited the choice behaviors and attitudes of pre-adolescent, adolescent, and adult decision makers within the same choice situation as well as between choice situations.…”
mentioning
confidence: 99%
“…In line with this finding, other research has previously shown that risk and ambiguity preferences are only weakly correlated [26,27]. Research on aging has yielded similar conclusions, demonstrating different lifespan patterns for attitudes towards risk and ambiguity [35,[62][63][64].…”
Section: Discussionsupporting
confidence: 75%
“…In yet another study Blankenstein and colleagues [46] found linear increases in ambiguity aversion from childhood through adulthood, while a follow-up study using a similar paradigm in participants in a similar age range found no age differences in ambiguity attitude [47]. Other studies have shown that younger children (ages 5 and 8) are ambiguity-neutral [80,81]. Given the lack of consistency in these results, future research will be required to better understand what factors might underlie these disparate patterns of age-related choice behaviour.…”
Section: Decisions Under Uncertainty (A) Decisions Under Ambiguitymentioning
confidence: 94%